Subsidy-driven firm growth: Does loan history matter? Evidence from a European Union subsidy program - Goel, Tirupam; Telegdy, Álmos; Banai, Ádám; Takáts, Előd (Journal of Corporate Finance, 2024)
Subsidies should target firms with profitable opportunities and insufficient funding, but this is difficult due to information asymmetry between firms and the government. We study how credit history of firms can help design more efficient subsidies. To this end, we combine data on non-repayable firm subsidies and the credit registry from Hungary. Using subsidy winners and losers as treated and control groups and leveraging variation in access to loans, we identify the differential impact of subsidies. While subsidies lead to an incremental impact on assets of loan-deprived as compared to loan-acquiring firms, the impact is transitory and fades after a few years. The impact on profitability follows a similar pattern despite the higher expected marginal value of capital for loan-deprived firms. Thus, loan deprivation is likely caused by borrower shortcomings instead of credit rationing by banks. In such cases, subsidies need not target loan-deprived firms.